SETTLEMENT EVALUATION AND BACK ANALYSIS OF THE GROUND DESIGN PARAMETERS ON THE SOIL IMPROVEMENT OF PRELOADING METHOD COMBINED WITH PVD - Intan Kamila Adiba; Januar Fery Irawan; Luthfi Amri Wicaksono (Universitas Jember, 2019)
The use of the preloading method, which combined with PVD, is now a common method of soil improvement that proved effective in increasing bearing capacity and reducing settlement on soft soil ground types like former rice fields. In order to reach an optimum effectiveness of soil improvement, an evaluation of the settlement should be done by reviewing the performance of soil improvement along with geotechnical instruments installed in the field. In this study, the back analysis method is used to determine the soil design parameters that are following the actual conditions in the field. The results obtained from the evaluation of settlement conducted is the difference between settlement calculation theoretically before the improvement of soil with the available field data of monitoring Settlement Plate. An average percentage of 118% was obtained from the calculation. In contrast, an average percentage of 2.87% was obtained as the difference between the final settlement prediction of Asaoka's with actual settlements based on Settlement Plate readings data in the field. The parameters of the soil results from the back analysis gave new values with each of the average of Ch= 0.02936; Cc= 0.27313; kv= 0.00005 m/day; and mv= 0.00064m2/kN. The difference between theoretical settlement recalculated using the soil parameter of the back analysis method with the actual settlement based on monitoring of Settlement Plate gave an average percentage of 12.66%. Metode Preloading yang dikombinasikan dengan PVD merupakan salah satu metode perbaikan tanah yang terbukti efektif dalam meningkatkan daya dukung tanah dan mengurangi settlement pada tanah jenis lunak seperti tanah bekas sawah. Agar perbaikan tanah yang dilakukan memiliki efektifitas optimum, perlu adanya evaluasi terhadap settlement yang terjadi dengan meninjau kinerja perbaikan tanah beserta instrumeninstrumen geoteknik yang terpasang di lapangan. Selain itu, dilakukan Metode Analisa Balik untuk mengetahui parameter desain tanah yang sesuai dengan keadaan sesungguhnya di lapangan. Hasil yang didapatkan dari evaluasi settlement yang dilakukan adalah selisih settlement secara teoritis sebelum adanya perbaikan tanah dengan settlement berdasarkan monitoring Settlement Plate di lapangan dalam persentase rata-rata sebesar 118%, sedangkan selisih antara final settlement prediksi Asaoka dengan settlement akhir berdasarkan monitoring Settlement Plate di lapangan mendapatkan persentase rata-rata sebesar 2,15%. Parameter-parameter tanah hasil dari analisa balik memiliki nilai baru dengan masing-masing rata-rata sebesar Ch= 0,02936; Cc= 0,27313; kv= 0,00005 m/hari; dan mv= 0,00064m2 /kN. Sedangkan untuk selisih antara settlement secara teoritis yang dihitung kembali menggunakan parameter tanah hasil analisa balik dengan settlement aktual berdasarkan data bacaan Settlement Plate mendapatkan persentase rata-rata sebesar 12,66%.